The location of cytochrome c on the surface of ultrathin lipid multilayer films using x-ray diffraction. - Pachence, J M (1987)
X-ray diffraction and spectroscopic techniques were used to characterize ultrathin fatty acid multilayers having a bound surface layer of cytochrome c. Three to six monolayers of arachidic acid were deposited onto an alkylated glass surface, using the Langmuir-Blodgett method. These fatty acid multilayer films were stored either in a 1 mM NaHCO3 pH 7.5 solution or a buffered 10 microM cytochrome c solution, pH 7.5. After washing extensively with buffer, these multilayer films were assayed for bound cytochrome c by optical spectroscopy. It was found that the cytochrome c bound only to the odd-numbered monolayer films (which have hydrophilic surfaces). The theoretical number of cytochrome c molecules bound to the ultrathin multilayer films having three or five monolayers was calculated as N = 1.2 x 10(13)/cm2 (assuming a hexagonally close-packed monolayer of protein), which would produce an optical density of 0.002 at a wavelength of 550 nm; for a three or five monolayer ultrathin film that was incubated with cytochrome c, OD550 approximately equal to 0.002. The protein was released from the film when treated with greater than 100 mM KCl solution, as would be expected for an electrostatic interaction. Meridional x-ray diffraction data were collected from the arachidic acid films with and without a bound cytochrome c layer. A box refinement technique, previously shown to be effective in deriving the profile structures of nonperiodic ultrathin films, was used to determine the multilayer electron density profiles. The electron density profiles and their autocorrelation functions showed that bound cytochrome c resulted in an additional electron dense feature on the multilayer surface, consistent with a bound cytochrome c monolayer. The position of the bound protein relative to the multilayer surface was independent of the number of fatty acid monolayers in the multilayer. Future studies will use these methods to investigate the structures of membrane protein complexes bound directly to the surface of multilayer films.